Outcomes utilizing imported liver grafts for recipients with hepatocellular carcinoma. Issue 3 (March 2017) - Battula, Narendra; Reichman, Trevor W.; Amiri, Yamah; Carmody, Ian C.; Galliano, Gretchen; Seal, John; Bugeaud, Emily; Bohorquez, Humberto; Bruce, David; Cohen, Ari; Loss, George E.
Abstract : Liver transplantation (LT) offers the best chance of survival in selected patients with hepatocellular carcinoma (HCC). Wait‐list mortality or dropout due to tumor progression can be significant, and therefore, timely transplantation is critical. Liver grafts discarded by outside organ procurement organizations are a potential source of grafts for low Model for End‐Stage Liver Disease tumor patients. The primary aim of this study was to assess the disease‐free and overall survival of patients with HCC transplanted with imported liver grafts (ILGs). Review of all patients transplanted for HCC between June 2005 and December 2014 was performed. Data on demographics, survival, and HCC recurrence were analyzed. During this time period, 59 out of 190 (31%) recipients with HCC received ILG. Of these 59 grafts, 54 were imported from within the region and 5 were from national offers (outside the region). The mean cold ischemia time for local liver grafts (LLGs) was 4.1 ± 1.5 hours versus 5.1 ± 1.4 hours for ILG ( P < 0.001). The 1‐, 3‐, and 5‐year patient survival was 90%, 85%, and 83% and 85%, 80%, and 79% for LLG and ILG ( P = 0.08), respectively. The observed disease recurrence rate for both LLG and ILG recipients was equivalent. The median wait‐list time for HCC recipients was 43 days (range, 2‐1167 days). In conclusion, with careful graft assessment, the use of ILGs results in comparable outcomes following LT and no increased risk of HCC recurrence. Use of ILGs maximizes the donor pool and results in a higher rate of transplantation for HCC recipients. Liver Transplantation 23 299–304 2017 AASLD .